Assessment of serum 25 (OH) Vitamin D status in elite Portuguese cycling athletes - Amorim, S.; Quintas, F.; Mendes, G.; Araújo, J. P.; Loureiro, N. (Journal of Science and Cycling, 2015)
Introduction: It is recognized that vitamin D has multiple effects in health (Autier, Boniol et al. 2014) and in athletic performance (Ogan and Pritchett 2013). It has been shown that it may have a role in the immune function, protein synthesis, inflammatory responses, regulation of cell growth and skeletal muscle physiology. However, vitamin D deficiency is common either in general population (Holick and Chen 2008) as in athletes (Farrokhyar, Tabasinejad et al. 2014). The endogenous synthesis via ultraviolet-B radiation through exposure to sunlight is the major source of vitamin D in humans. The 25(OH) Vitamin D is used as the clinical measure of vitamin D status (Willis, Peterson et al. 2008). However optimal concentration thresholds are not yet well determined.